Synthesis of 2, 3-diaza-anthraquinones via the bidentate Lewis acid catalysed inverse electron-demand Diels–Alder (IEDDA) reaction. Issue 5 (13th April 2017) - Hong, Longcheng; Ahles, Sebastian; Strauss, Marcel A.; Logemann, Christian; Wegner, Hermann A.
Abstract : A new synthesis of aza-anthraquinones and substituted anthraquinones via bidentate Lewis acid catalysis has been developed. Abstract : The bidentate bisborane Lewis acid catalysed inverse electron-demand Diels–Alder (IEDDA) reaction of 1, 4-naphthoquinones (1, 4-NQs) with 1, 2, 4, 5-tetrazine (TZ ) has been developed for the synthesis of 2, 3-diaza-anthraquinones (2, 3-DAAQs). Only due to the coordination ofTZ with the bisborane catalyst, the IEDDA reaction of electron-deficient 1, 4-NQs is possible. The use ofTZ as the nitrogen source provides an efficient strategy to the 2, 3-diaza-anthraquinones. The 2, 3-DAAQs themselves are suitable dienes for a second bidentate Lewis acid catalysed IEDDA reaction with various dienophiles to afford substituted AQs. AQs have been discussed as privileged structures for applications in medicinal as well as materials science.